STUDY OF ANTIOXIDANT AND PREBIOTIC PROPERTIES OF XYLOOLIGOSACCHARIDES AND POFYPHENOLS FROM SECONDARY BIOPRODUCTS OF CEREAFS - D. R. Zyaitdinov; A. V. Evteev; A. V. Bannikova (Современная наука и инновации)
Novel biotechnological approaches are suggested for the processing of cereal by-products into functional food concentrates: dietary fiber, polyphenols and xylooligosaccharides (XOS). The study shows a complex biotechnology of oat, wheat and rye bran biotransformation into functional ingredients with antioxidant and prebiotic properties.